2007
DOI: 10.1007/s11764-007-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine sequelae of cancer and cancer treatments

Abstract: Recognition and awareness of endocrine sequelae of cancer treatments may permit for early detection and appropriate follow-up care for cancer survivors, thus improving their overall health and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 168 publications
1
31
0
3
Order By: Relevance
“…67 A direct explanation for this is not yet available, but it is hypothesized that hormonal alterations induce obesity, which subsequently induces insulin resistance and other components of the metabolic syndrome. Alternatively, hormonal alterations might be induced by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…67 A direct explanation for this is not yet available, but it is hypothesized that hormonal alterations induce obesity, which subsequently induces insulin resistance and other components of the metabolic syndrome. Alternatively, hormonal alterations might be induced by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In adult survivors of childhood cancers, endocrine toxicity, including thyroid disorders, is a common long-term complication of cytotoxic treatments (9). Conversely, cytotoxic treatments seem to alter thyroid function in a relatively small portion of adult patients (5).…”
Section: Thyroid and Cytotoxic Anticancer Agentsmentioning
confidence: 99%
“…In the present study, we found normal BMI and normal percentage fat in NHL survivors. Hypothyroidism, which can contribute to obesity and is reported in survivors, especially after local radiotherapy [49][50][51], did not occur in this group of survivors.…”
Section: Discussionmentioning
confidence: 50%